The Ovarian Volume in Girls Presented as Precocious Puberty - Onder Durmaz; Erdem Fatihoglu; Berna Hatun Ozkan; Kemal Bugra Memis; Sonay Aydin (Journal of Medical Ultrasound)
Background: Isosexual precocious puberty (PP) is defined as the appearance of secondary sexual characteristics before the age of 8 years in girls and before the age of 9 years in boys. The aim of this study was to evaluate the association of ovarian volume and bone age measurements with the number of symptoms in female patients diagnosed with PP. Methods: The dataset includes pelvic ultrasound and bone age tests from 96 girls diagnosed with PP who presented to a tertiary hospital’s pediatric outpatient clinic with signs and symptoms of early puberty between January 1, 2020, and January 1, 2021. The study included 96 healthy ladies of the same age as a control group. Results: A total volume >2.75 was shown to predict the existence of pubertal pre with 79.2% sensitivity and 90.6% specificity (area under the curve [AUC]: 0.903; P = 0.001). A total volume of >3.25 predicted the existence of 2 or more symptoms in patients with PP, with a sensitivity of 72.1% and a specificity of 98.1% (AUC: 0.917; P = 0.001). Conclusion: To the best of our knowledge, no study has been published that investigates the relationship between the number of symptoms at the time of presentation and ovarian volume and bone age in girls with PP. Our investigation, which involved 192 female participants (96 patients and 96 controls), revealed a statistically significant correlation between the frequency of symptoms indicating early puberty and a rise in both ovarian capacity and bone age.